The use of dark field photomicrography in the assessment of sperm motility in buffaloes, bulls, and bucks - Torres, Eduardo B. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1999)
The adoption of dark field photomicrography as an objective measure of sperm motility is herein presented. Drops of buffalo, bull and buck semen (fresh or frozen) were placed on prewarmed glass slides, covered with coverslips and photographed (1- and 2-second exposure time, low and high power magnification) to identify the tracks of motile spermatozoa.